Transcrição e reconstrução digital: utopias possíveis de Sergio Bernardes - Claro, Marcel Alessandro (2017)
The digital models allow us to test and visualize a conceived space and analyze all its possibilities of accomplishment: its plastic, aesthetics, structure, connection with the surroundings and other parameters for the better understanding of the project. However, the greatest advantage of digital models and simulations lies in the experience and spatial experience of non-built projects, where psychological sensations and dimensions will produce answers that may or may not have been imagined by the architect who designed it. This dissertation brings the opportunity to experience the spaces designed by Sergio Bernardes for the Tropical Hotel of Manaus, through new images and video, in order to find principles and ideals related to the technological utopias of modernity present in the conception of the project. Transcription and Digital Reconstruction is a three-dimensional space experience and analysis method where the collected documentation (original drawings of the plants and cuts, pictures of models, sketches and perspectives) are generated in digital platforms (CAD and BIM) for the subsequent digital reconstruction of the design in 3D modeling software. The search for concepts, ideas and influences in the design process, together with the Digital Transcription and Reconstruction method of non-built buildings, allows us to create a new iconography, a virtual space that admits explorations, sensations, experiences and visualizations of the project to the comparing the researcher 's ideas with the current analyzes of the projects of Sergio Bernardes in order to enrich, more and more, the academic and scientific works on un - built architecture projects and projects of this architect fundamental to Brazilian architecture